The impact of amyloid‐beta and tau on prospective cognitive decline in older individuals. Issue 2 (21st January 2019) - Sperling, Reisa A.; Mormino, Elizabeth C.; Schultz, Aaron P.; Betensky, Rebecca A.; Papp, Kathryn V.; Amariglio, Rebecca E.; Hanseeuw, Bernard J.; Buckley, Rachel; Chhatwal, Jasmeer; Hedden, Trey; Marshall, Gad A.; Quiroz, Yakeel T.; et al.
Abstract : Objectives: Amyloid‐beta (Aβ) and tau pathologies are commonly observed among clinically normal older individuals at postmortem and can now be detected with in vivo neuroimaging. The association and interaction of these proteinopathies with prospective cognitive decline in normal aging and preclinical Alzheimer's disease (AD) remains to be fully elucidated. Methods: One hundred thirty‐seven older individuals (age = 76.3 ± 6.22 years) participating in the Harvard Aging Brain Study underwent Aβ ( 11 C‐Pittsburgh compound B) and tau ( 18 F‐flortaucipir) positron emission tomography (PET) with prospective neuropsychological assessments following PET imaging (mean number of cognitive visits = 2.8 ± 1.1). Tau and Aβ PET measures were assessed in regions of interest (ROIs) as well as vertex‐wise map analyses. Cognitive change was evaluated with Memory and Executive Function composites. Results: Higher levels of Aβ and tau were both associated with greater memory decline, but not with change in executive function. Higher cortical Aβ was associated with higher tau levels in all ROIs, independent of age, and very elevated levels of tau were observed primarily in clinically normal with elevated Aβ. A significant interaction between tau and Aβ was observed in both ROI and map‐level analyses, such that rapid prospective memory decline was observed in participants who had high levels of both pathologies. Interpretation: Our results are consistent with the supposition that both Aβ and tau are necessary for memory decline in the preclinical stages of AD. These findings may be relevant for disambiguating aging and early cognitive manifestations of AD, and to inform secondary prevention trials in preclinical AD. Ann Neurol 2019;00:1–3ANN NEUROL 2019;85:181–193.